Pengaruh Kompetensi Pedagogik dan Aktivitas Belajar Terhadap Kemandirian Anak Rentan Jalanan Semarang - Hidayati, Febria Tri; Utsman, Utsman (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2019)
The purpose of study to anaysize of pedagogoic competence of tutor, learning activity and independence of street vulnerable children, the influence of pedagogic competence of tutor toward independence of street vulnerable children, the influence of learning activity toward independence of street vulnerable children, the influence of pedagogic competence and learning activity toward children independence vulnerable to the streets. research using quantitative expost-facto method with 33 as sample using propability proportionate random sampling technique. The data collection tool used is a questionnaire. The results obtained that there is the influence of pedagogic competence on independence of street vulnerable children, F test result Fcount = 15,509 > Ftable = 3,30. and T test shows Thitung = 3,938 > Ttable=2,042. there is the influence of learning activities on the independence of street vulnerable children, F test result Fcount = 33.440 > Ftable = 3.30, and T test is thitung = 5,783 > Ttable=2,042. there is the influence of pedagogic competence and learning activities on the independence of street vulnerable children, Test F Fcount = 17,099 > Ftable = 3,30, (T test) tcount = 3,669 > Ttable=2,042.